Governing medical knowledge commons - Strandburg, Katherine Jo, 1957-; Frischmann, Brett M.; Madison, Michael J., 1961- (Cambridge : Cambridge University Press, 2017)
Governing Medical Knowledge Commons makes three claims: first, evidence matters to innovation policymaking; second, evidence shows that self-governing knowledge commons support effective innovation without prioritizing traditional intellectual property rights; and third, knowledge commons can succeed in the critical fields of medicine and health. The editors' knowledge commons framework adapts Elinor Ostrom's groundbreaking research on natural resource commons to the distinctive attributes of knowledge and information, providing a systematic means for accumulating evidence about how knowledge commons succeed. The editors' previous volume, Governing Knowledge Commons, demonstrated the framework's power through case studies in a diverse range of areas. Governing Medical Knowledge Commons provides fifteen new case studies of knowledge commons in which researchers, medical professionals, and patients generate, improve, and share innovations, offering readers a practical introduction to the knowledge commons framework and a synthesis of conclusions and lessons. The book is also available as Open Access.
Introduction : Knowledge commons and the road to medical commons -- The knowledge commons framework -- Leviathan in the commons : biomedical data and the state -- Centralization, fragmentation, and replication in the genomic data commons -- Genomic data commons -- Population biobanks' governance: a case study of knowledge commons -- The sentinel initiative as a knowledge commons -- Cancer : from a kingdom to a commons -- The greatest generational impact : the open neuroscience movement as an emerging knowledge commons --Better to give than to receive : an uncommon commons in synthetic-biology -- Governance of biomedical research commons to advance clinical translation : lessons from the mouse model community -- Constructing interdisciplinary collaboration : the oncofertility consortium as an emerging knowledge commons -- The application of user innovation and knowledge commons governance to mental health -- Challenges and opportunities in developing and sharing solutions by patients and caregivers : the story of a knowledge commons for the patient innovation project -- Chronic disease, new thinking and outlaw innovation : patients on the edge in the knowledge commons -- The North American Mitochondrial Disease Consortium : a developing knowledge commons -- The Consortium of Eosinophilic Gastrointestinal Disease Researchers (CEGIR) : an emerging knowledge commons -- Conclusion : governing knowledge commons : an appraisal.
Title from publisher's bibliographic system (viewed on 24 Oct 2017).
Keywords: Medical technology